Capillary Electrophoresis 2008
DOI: 10.1007/978-1-59745-376-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis of Oxidative Dna Damage

Abstract: Urinary 8-hydroxy-2'-deoxyguanosine (8OHdG) is an excellent marker of oxidative DNA damage. Until now, urinary 8OHdG has been measured by high-performance liquid chromatography with electrochemical detection. A simple and sensitive method for the analysis of urinary 8OHdG by capillary electrophoresis with end-column amperometric detection has been developed and is described in this chapter. A single-step solid-phase extraction procedure was optimized and used for extracting 8OHdG from human urine. To improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Furthermore, it is known that interactions between DNA and ROS produce DNA strand break and base modification, which are frequently assessed by measurement of 8-OHdG levels . Interestingly, a recent study demonstrates that urinary 8-OHdG is an excellent marker for oxidative DNA damage (Xu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that interactions between DNA and ROS produce DNA strand break and base modification, which are frequently assessed by measurement of 8-OHdG levels . Interestingly, a recent study demonstrates that urinary 8-OHdG is an excellent marker for oxidative DNA damage (Xu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…capillaries or smaller, it has been found that the voltage drop across the capillary is great enough that interference with the detection circuit is minimal [17]; however, a shift in the half-wave potential is possible [18]. This configuration has been used for high-throughput separations [19], analysis of insecticides [20], and quantitation of DNA damage [21].…”
Section: Introductionmentioning
confidence: 99%
“…Capillary electrophoresis with UV or electrochemical detection has been used to analyze the oxidative damage of DNA. However, these assays exhibited low sensitivity [20]. In addition, capillary electrophoresis coupled to laser-induced fluorescence (CE-LIF) was developed to sensitively measure endogenous damage in mitochondrial and genomic DNA [21].…”
Section: Introductionmentioning
confidence: 99%